Silo-Best® for sorghum silages - Bolsen, K.; Ilg, H.; Hinds, M. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
Silo-Best lowered the ensiling temperature and increased the dry matter recovered from the silo by over 5 percentage units (82.3 vs. 77.3%). Calves fed the control silage gained faster and consumed more feed, but those fed treated silage were slightly more efficient. The more efficient gain and lowered shrink loss for Silo-Best silage gave 6.4 extra pounds of calf gain per ton of crop ensiled.
Keywords: Beef; Sorghum silage; Temperature; Dry matter